Method for producing aggregate and aggregate
Patent Information
- Application Number
- JP2024541792
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-12
- Filing Date
- 2023-01-12
- Publication Date
- 2025-03-06
- Estimated Expiration
- 2043-01-12
AI Technical Summary
Existing methods for isolating carbon dioxide using Olivin are complex, expensive, and not suitable for industrial-scale applications, with low conversion rates and high energy consumption.
A method involving the dehydration of magnesium silicate hydrates, such as serpentinite, through controlled heat treatment and crushing to produce a dehydrated form that is then compressed to form aggregates capable of capturing carbon dioxide, utilizing renewable energy and precise temperature control to enhance reactivity.
This method allows for efficient capture of carbon dioxide with a high conversion rate using minimal energy input, producing aggregates suitable for construction materials like concrete, while reducing greenhouse gas emissions.
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an aggregate having sequestered CO2, and to the aggregate.
[0002] In the construction industry, natural and artificial aggregates are called aggregates. They come, for example, from natural deposits or are produced during recycling of building materials or as industrial by-products. Alternative terms in the construction industry that are not in practical use but have roughly the same meaning are concrete aggregate, mineral mixture, mineral mixture, or mineral material.
[0003] In principle, aggregates can be processed together with a binder (usually cement) and water to form concrete. However, asphalt is also a mixture of aggregates and bitumen. The particle shape, strength and grading curve of the aggregates, among others, can affect the properties of the resulting building material at this point.
[0004] Binder-free aggregates are used, for example, to create unpaved roads, infiltration and defrost packs, capillary breaks and similar fills.
[0005] Carbon dioxide (CO2) acts as a greenhouse gas in the atmosphere and is considered one of the main causes of anthropogenic global warming. In addition to radically reducing CO2 emissions, parallel efforts are being made to bind the CO2 already present in the atmosphere. By binding CO2, manufacturing processes that generate large amounts of CO2, such as cement production, can also be made CO2-neutral.
[0006] CO2 sequestration specifically refers to the removal of CO2 from the atmosphere, ideally combined with other substances so that it cannot escape again. Various proposals for this are known. One possibility is to use olivine.
[0007] Olivine is a mineral with the common composition A2[SiO4], with a variety of divalent ions occurring for A, such as magnesium (forsterite, Mg2SiO4), iron (Fe2SiO4, fayalite), manganese (Mn2SiO4, tefloite), and, since olivine is a solid solution series, other ions and combinations of various cations also occur.
[0008] The patent literature on accelerating the sequestration of carbon dioxide in reactions with olivine is very extensive. Many methods for sequestrating CO2 with olivine are based on the following principles and differ mainly in the way the reaction is accelerated:
[0009] [ka]
[0010] According to WO 2007 / 069902, the reaction should be accelerated by grinding and adjusting a certain pH value, WO 2008 / 140821 and WO 2008 / 061305 propose to accelerate the reaction by high temperature, high CO2 partial pressure, and high fineness of olivine, WO 2008 / 101293 proposes the addition of ammonium, WO 2007 / 106883 proposes the addition of a base, and US 4944928 proposes the addition of hydrochloric acid.
[0011] In addition to these processes, there are many other processes that can accelerate the sequestration of carbon dioxide during reaction with olivine, but all of these processes use complex technologies and expensive starting materials.
[0012] The CO2min project attempts to combine such olivine carbonation with cement production. The aim is to capture CO2 emissions from the cement industry by carbonating olivine. As a result, cement production will continue unchanged, preserving the existing high-temperature process. The resulting carbon dioxide is combined with olivine in the form of magnesium carbonate and SiO2 by reaction. This generated material is then added to the cement and disposed of. However, it is obviously not possible to completely convert olivine into magnesium carbonate (see D. Kremer, H. Wotruba, "Separation of products from mineral sequestration of CO2 with primary and secondary materials", Minerals, Vol. 10 (2020), pp. 1098 ff.). In this project, very high CO2 partial pressures (17 bar) and high temperatures (175 °C) were used. Despite autoclaving, the conversion of olivine is low, and very large quantities of olivine are required to compensate for the low conversion. The process technology chosen is also probably not suitable for binding carbon dioxide on an industrial scale.
[0013] Another idea of binding carbon dioxide through reaction with olivine was also developed in the Netherlands (see R.D. Schuiling, P. Krijgsman, "Enhanced Weathering: An effective and cheap tool to sequester CO2", Climate Change, Vol. 74 (2006), pp. 349-354). Olivine is spread on arable land or spread on coasts. When olivine is dissolved in magnesium ions, precipitation or seawater converts HCO3 - Carbon dioxide can be simultaneously absorbed in the form of ions.
[0014] [ka]
[0015] However, laboratory experiments at the University of Hamburg have shown that the described reactions do not occur in the described way: even if olivine were spread over the entire arable land of the world, it would only capture 0.2% of the world's carbon dioxide emissions (see T. Amann et al., "Enhanced weathering and related element fluxes- a cropland mesocosm approach," Bio geosciences, Vol. 17 (2020), pp. 103-109). Summary of the Invention [Problem to be solved by the invention]
[0016] The underlying objective of the present invention is to provide an efficient method for producing aggregates that are also capable of sequestering CO2. [Means for solving the problem]
[0017] According to the invention, this object is achieved by means of a method having the features of claim 1 and by means of an aggregate having the features of claim 15. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Further advantageous embodiments are described in the dependent claims and the further description.
[0019] According to claim 1, first, at least 20% by weight, preferably at least 40% by weight, more preferably at least 60% by weight, and even more preferably at least 80% by weight of magnesium silicate hydrate (Mg3Si2O5(OH)4, Mg3Si4O 10A starting product is provided that contains magnesium silicate hydrates (OH)2). An example of this is serpentine. Serpentine is a metamorphic rock formed by natural transformation, especially weathering, of ultramafic rocks. Advantageously, the starting material should not contain any SiO2 and should not contain any substances that release SiO2 during the heat treatment. SiO2 may react with magnesium silicate hydrates during the subsequent heat treatment, thereby degrading the quality of the product.
[0020] The key mineral of ultramafic rocks is olivine, a mixed crystal series of fayalite (Fe2SiO4), forsterite (Mg2SiO4), tefloite (Mn2SiO4) and other minerals of the A2[SiO4] type. Natural olivine deposits have been recorded, and olivine is often an iron-bearing, magnesium-rich material.
[0021] The basic reactions that occur during weathering are as follows, shown here in simplified form starting with forsterite (Mg2SiO4):
[0022] [ka]
[0023] Magnesium silicate hydrate (Mg3Si2O5(OH)4, Mg3Si4O 10 (OH)2) can exist in lizardite, antigorite, talc and other forms. It should be noted that the stoichiometric water content of antigorite can be lower (in the range of 13% by weight) than the test-determined water content of 16% to 20% by weight. This can be explained by the fact that some materials are very fine and water can adhere to their surfaces.
[0024] Similarly, such deviations from stoichiometry apply to the ratio between Mg and Si. Furthermore, foreign ions such as Fe may be incorporated into the reaction products. However, other reaction products such as hydromagnesite, hematite, magnetite or gibbsite may also be produced. This depends in each case on the exact composition of the starting products. All or part of the reaction products may contain iron, carbonate, alkali or other foreign ions.
[0025] The starting product is 0.1m 2 The powder is crushed to a fineness corresponding to a BET surface area of 0.5 m / g or finer. The BET surface area can be determined using the BET method according to the standard DIN ISO 9277:2003-05 "Determination of the specific surface area of solids by gas adsorption". 2 / g BET surface area is preferred, and 1.0 m 2 It is even more preferred that the BET surface area is 0.01 to 0.01 g / g or finer. This can be achieved by grinding. Depending on the source of the magnesium silicate hydrate, grinding in the sense of the present invention can also take place during or as a result of mining, extraction or, more generally, production.
[0026] After the starting product is prepared, it is homogenized if necessary.The serpentine rock mentioned as an example is a material from natural deposits.Experience shows that it is not available in pure form or homogenized state.Homogenization can be carried out, for example, using a mixer or simultaneously with crushing to the desired fineness.
[0027] The homogenized starting product is subsequently at least partially dehydrated from bound water by means of heat treatment in a heat treatment unit. The heat treatment proposed here is also called tempering or calcination. Bound water is also called crystal water. Bound water must be differentiated from unbound water, which can be considered as free H2O. Complete dehydration can be achieved at great expense. According to the invention, the content of bound water should be reduced by at least 60%, preferably at least 80%, more preferably at least 90%.
[0028] For the heat treatment, the starting product can be heated to temperatures between 180 ° C and 1000 ° C. Depending on the fineness present, heating for only a few minutes may be sufficient. Temperatures between 300 ° C and 800 ° C are preferred, temperatures between 500 ° C and 700 ° C are even more advantageous.
[0029] In this step, the magnesium silicate hydrate (Mg3Si2O5(OH)4, Mg3Si4O 10 The (OH)2) is at least partially converted to dehydrated magnesium silicate hydrate, which can be represented in simplified form as xMgO·SiO2·yH2O by dehydration. Dehydration here refers to the reduction of water of crystallization or water in the transformed starting product.
[0030] The basic chemical process is again simplified as follows:
[0031] [ka]
[0032] Equation (3) produces a nearly amorphous reaction product with a Mg to Si ratio of 1.5 to 2 and a bound water content of about 3%. The reaction product produced by equation (4) has an even lower Mg to Si ratio. Thus, the variables a, b, c, x, y and z will depend in each case on the exact composition of the starting product and the processing parameters.
[0033] After dehydration, the content of bound water in the converted and dehydrated starting product is preferably less than 10% by weight, more advantageously less than 5% by weight, even more preferably less than 3.5% by weight, particularly preferably less than 2.5% by weight.
[0034] The dehydrated starting product is therefore present as a multiphase product. Other possible secondary phases are hematite, magnetite, enstatite, feldspar, pyroxene, quartz and amorphous phases.
[0035] Once the starting product has been dehydrated, it can be brought into contact with CO2. Here, CO2 reacts with the dehydrated magnesium silicate hydrates present (xMgO·SiO2·yH2O). CO2 is mainly bound to the resulting magnesium carbonate (MgCO3) and / or magnesium carbonate hydrates (MgCO3*mH2O). Magnesium carbonate is called magnesite by its mineral name. Magnesium carbonate hydrates include, for example, barintonite (m=2), nesquehonite (m=3) and lancefordite (m=5). In addition, basic magnesium carbonate hydrates also exist, such as artinite, hydromagnesite and dypingite.
[0036] The basic chemical process can be simplified and generalized as follows:
[0037] [ka]
[0038] where q, x, and y represent the corresponding variables, which may be zero in some cases. It should also be noted that in equation (5), the dehydrated magnesium silicate hydrate appears only as xMgO·SiO2·yH2O, since it is (incompletely) dehydrated. Ideally, the above reaction according to the invention produces little or no Mg(OH)2.
[0039] Before or after the step of contacting the dehydrated starting product with CO2, it is intended to be pressed and compressed into a solid body to produce aggregate. With the optional addition of a binder, this can produce an essentially solid body that can be used as aggregate. SiO2 should not be added before pressing and compacting, otherwise there will be too much CaO, Al2O3 or other additives to bind the SiO2.
[0040] In accordance with the present invention, it has been recognised that by removing the water of crystallisation from natural materials such as weathered ultramafic rocks, e.g. serpentine, an intermediate material suitable for highly binding CO2 can be produced.
[0041] In this way, large amounts of CO2 can be bound with relatively little energy input. For example, using the method of the present invention, about 0.6 tonnes of CO2 can be bound in a few hours with about 1 tonne of serpentine.
[0042] Preferably, the heat treatment of the starting product is carried out at a temperature of at least 550° C. and / or at most 750° C., and the starting product is heat treated for at least 5 minutes, advantageously 15 minutes, preferably 30 minutes and even more preferably at least 60 minutes.
[0043] It is advantageous to maintain the dehydration temperature characteristic of a particular material as accurately as possible, with deviations of less than 20 °C. If the temperature during heat treatment is too low, magnesium silicate hydrates (for example, serpentine) are not dehydrated or are dehydrated insufficiently. If the temperature is too high, magnesium silicate hydrates are mainly converted into olivine, which has poor reactivity. Only in a narrow temperature range does dehydration occur, with little or no olivine formation. On the contrary, the dehydrated starting product is formed in the form of an X-ray amorphous phase with a low residual water content of 2-5% by mass. This phase has high reactivity and is the target product of the heat treatment.
[0044] It is therefore preferred that the heat treatment unit has an essentially uniform temperature distribution. This makes it possible to achieve good dehydration without producing unwanted by-products. It is therefore advantageous not to heat the furnace directly with a flame in order to maintain the desired dehydration temperature in the furnace as accurately as possible and for the majority of the residence time of the material. In this case, the material is temporarily exposed to very high temperatures, which leads to the formation of olivine. For example, the temperature distribution in a directly heated rotary kiln is too uneven. It is therefore advantageous if a rotary kiln, in particular an indirectly heated rotary kiln without a direct flame in the reaction chamber, is used as the heat treatment unit. The temperature during the heat treatment, also called the calcination temperature, can be controlled particularly accurately in an electrically heated furnace. Electrical heating should be used in particular to accurately maintain the target temperature in the furnace chamber. It is advantageous to heat the kiln with electrical energy from a renewable energy source, since no CO2 emissions and exhaust gases are produced and no fuel is consumed. In contrast, it is also possible to preheat using other heat sources, in particular heat exchangers, which remove part of the heat from the dehydrated starting product, for example from the calcined serpentine, thereby cooling it while this heat is supplied to the uncalcined serpentine. The use of exhaust gases from combustion processes should be avoided as far as possible, since this can result in uncontrolled binding of, for example, CO2.
[0045] In order to achieve a sufficient residence time at the target temperature, rotary kilns are preferred since they have a large volume and therefore can achieve a high throughput. Moreover, rotary kilns are characterized by good thermal efficiency.
[0046] Heat treatment is particularly efficient with small particle size magnesium silicate hydrates, such as crushed serpentine, where particle-bound water is removed more quickly and efficiently. At the same time, low water vapor partial pressures in heat treatment units, such as furnace chambers, promote the formation of reactive phases to bind CO2. Low water vapor partial pressures can be achieved by air purging the furnace chamber.
[0047] After heat treatment, the dehydrated starting product, for example reinforced serpentine, is usually available as a powder. This powder can be directly contacted with CO2 or pre-pressed into a solid. Further crushing is not necessary and has even been found to have a negative effect on further processing.
[0048] Pressing and compressing the dehydrated starting product is carried out until its solids are 1 mm 3 ~30,000mm 3 These sizes are particularly suitable for use as aggregates.
[0049] It is further indicated that the pressing and compaction are preferably carried out in such a way that the solid is formed with a porosity of less than 30% by volume, preferably less than 20% by volume, more advantageously less than 10% by volume, since on the one hand, when subsequently contacted with CO2, due to the porosity, the latter can easily reach the material that is not present on the surface, and on the other hand, aggregates of this type are particularly well used.
[0050] The higher the compaction of the solids and the lower the porosity of the solids, the higher the subsequent strength of the aggregate, also known as sand or gravel. The compacted solids should be firm enough to avoid damage during subsequent processing.
[0051] If the dehydrated starting product is contacted with CO2 after pressing and compacting, the dehydrated starting product should be pressed into pellets for further processing.
[0052] Fully automatic tablet presses are particularly suitable for this purpose. During the pressing process, a small amount of dehydrated starting product available in powder form is filled into a die and compressed with a suitable tool. After the pressing process, the porosity of the pressed pellets can be determined from the ratio of the bulk density to the pure density.
[0053] The porosity should be less than 30% by volume, advantageously less than 20% by volume, preferably less than 10% by volume, and better still less than 5% by volume. However, it is advantageous if a low residual porosity remains to allow CO2 to permeate the pellets.
[0054] The pressing process can be improved by adding water, organic liquids and other substances that facilitate the compression of the powder. Low porosity after the pressing process ensures high strength. Furthermore, the pellets are preferably available in green strength after the pressing process, which facilitates transportation and further processing such as treatment with CO2.
[0055] If the powder is mixed with other substances before the pressing process, additional chemical reactions can provide additional strength, further increasing the strength of the hardened pellets. These substances include, for example, NaOH, KOH, Ca(OH)2, and other compounds that release alkali and / or alkaline earth elements, sodium aluminate, coal fly ash, trass, reinforced clay, and other substances that contain Al2O3, CaO, and / or alkali in a form that can react with SiO2 during treatment with CO2 (preferably in an autoclave). Materials containing alite or belite should not be added, as they may have a negative effect on hardening.
[0056] After heat treatment, the dehydrated magnesium silicate hydrate is available as a powder and can be pressed, if necessary, with the addition of other substances. The pressing process makes it possible to achieve green strength, which facilitates further processing. In contrast, the pressing process does not give a permanent strength that allows it to be used as gravel.
[0057] In order to build up high compressive strength in the pressed particles, chemical reactions are required to solidify and hold the structure. On contact with CO2, several reactions occur, which contribute in different ways to the permanent strength of the gravel. One reaction is the production of magnesium carbonate or magnesium carbonate hydrate from the dehydrated magnesium silicate hydrate. This takes place with the consumption of dehydrated magnesium silicate hydrate. The magnesium combines with the CO2 and SiO2 is deposited as an amorphous phase. This results in an increase in volume as the CO2 penetrates the pressed particles from the outside. If magnesium carbonate hydrate is produced, the increase in volume is even greater. The greater the increase in volume during the chemical reaction, the more porosity remains after pressing. The lower the porosity, the higher the strength. Furthermore, the formation of new phases solidifies all the phases, thus building the permanent strength required for use as gravel.
[0058] The second reaction, which causes permanent solidification of the pressed particles, is the hydration of the dehydrated magnesium silicate hydrates. In this process, phases such as antigorite, talc and lizardite are formed. This hydration reaction can be compared to the hardening of hardened cement paste, with the difference that MSH is formed instead of CSH.
[0059] The third chemical reaction that causes solidification is the chemical reaction of the SiO2 from carbonation with the substances added before the particles are pressed. In the presence of reactive aluminum and alkali, NASH phases are formed, which also occur during the solidification of geopolymers. In the presence of reactive CaO, SiO2 can also be converted to CSH.
[0060] All three reactions contribute to the reduction of porosity and solidification of the pressed particles, which can then be used as gravel for concrete production and other purposes. The extent of the three reactions can be controlled by external conditions such as pressure, temperature, and the availability of CO2, chemical composition.
[0061] If pressing is performed after contact with CO2, the pressed particles do not contain dehydrated magnesium silicate hydrates, but magnesium carbonate and SiO2, and possibly other phases. This means that the formation of magnesium carbonate and magnesium carbonate hydrates can no longer contribute to strength formation, or can only contribute to a small extent. Instead, solidification is based on the chemical reaction of the substances added after contact with CO2. If reactive aluminum and reactive alkalis are added, they react with the amorphous SiO2 from the sequestration, resulting in NASH, which allows strength formation. The same is true for the addition of reactive CaO and the formation of CSH. Dehydrated magnesium silicate hydrates can also be added, which is converted to MSH. Other organic and inorganic binders can also be used.
[0062] The dehydrated starting product remains powdery or forms a powder when contacted with CO2 before pressing and compacting. This process is explained in more detail below. Therefore, to produce aggregates, the dehydrated magnesium silicate hydrate should be solidified by contacting with CO2.
[0063] This solidification is advantageously based on the reaction of amorphous SiO2 (formula 5) with the added substances. These include substances that introduce Al2O3, alkali or CaO in reactive form, such as hard coal fly ash, granulated blast furnace slag, reinforced clay, sodium aluminate, NaOH, KOH. Portland cement clinker should not be added. After the addition, intensive homogenization is possible and advantageous. If the materials are mixed in dry form, joint grinding is conceivable. In addition to the above-mentioned materials, other binders, such as organic adhesives, can also be used to bind the gravel particles.
[0064] The pretreated material can then be pressed into a solid body. In this process, the porosity after the pressing process should be less than 30% by volume, preferably less than 20% by volume, more advantageously less than 10% by volume, and even better less than 5% by volume. The compressed solid may contain a small amount of water. This water can be added before or after the pressing process. The gravel particles are hardened and form NASH phases due to the reaction of the amorphous SiO2 from the sequestration with the alkali and Al2O3 from the added material. At the same time, the formation of CSH phases occurs in the presence of reactive CaO or through other chemical reactions or physical processes.
[0065] These reactions are accelerated by raising the temperature to 40° C., better still 60° C., for at least 2 hours, advantageously 12 hours, preferably 24 hours, which increases the strength of the gravel particles. The solids are therefore advantageously heat treated at a temperature of at least 40° C., preferably at least 60° C., for at least 2 hours, in particular at least 24 hours. The gravel particles should be protected from drying. This can be done with an appropriate level of humidity in a processing device such as an autoclave. Preferably, the atmosphere is saturated with respect to water vapor.
[0066] Regardless of whether the contacting of the dehydrated starting product with CO2 takes place before or after the production of the solid, the contacting can advantageously be carried out in a closed vessel, in particular in an autoclave, or in an overpressure vessel. In this way, the CO2 binding process can be optimized, for example, by adjusting the CO2 partial pressure in the autoclave, the temperature present and / or the water content in the atmosphere.
[0067] CO2 is bound particularly quickly if the dehydrated starting product is contacted with CO2 after pressing and compression at a CO2 partial pressure of at least 0.1 bar, or if the dehydrated starting product is contacted before pressing and compression at a CO2 partial pressure of at least 0.0003 bar, preferably 0.0010 bar. During the contact of the dehydrated starting product with CO2, the temperature during the reaction can be at least 30°C, preferably above 50°C. The CO2 partial pressure can be less than 0.5 bar.
[0068] Additionally, it may be preferable to add a substance, such as a sugar or other organic additive, to the dehydrated starting product prior to or during contact of the dehydrated starting product with CO2, which reduces the formation of magnesium silicate hydrate, which has the effect of increasing the amount of magnesium carbonate produced.
[0069] If pressing and compacting are followed by treatment or contact with CO2, it is favorable for the production of magnesium carbonate or magnesium carbonate hydrate if the solids, e.g., pellets, are moist. The reaction occurs faster in the presence of water because the activation energy for the reaction is lower.
[0070] The introduction of water can be achieved by spraying the pressed pellets with water. It is also possible to create an atmosphere in the autoclave saturated with respect to water vapor. A combination of the two variations is particularly suitable for introducing water.
[0071] The presence of water promotes the dissolution of dehydrated starting products such as reinforced serpentine and the production of magnesium carbonate and SiO2. In place of SiO2, other silicon-containing phases can also be formed if CaO, Al2O3 and / or other alkali-providing starting materials are present.
[0072] On the other hand, the presence of water can also allow the formation of magnesium silicate hydrates. When this occurs, the formation of magnesium silicate hydrates also contributes to the strength of the aggregate. However, the formation of magnesium silicate hydrates is a competing reaction to the formation of magnesium carbonate or magnesium carbonate hydrates, thus reducing the CO2 binding capacity.
[0073] For this reason, it is desirable to control and, if necessary, reduce the formation of magnesium silicate hydrates. This can be done by selecting the reaction parameters or by adding substances that can inhibit the formation of magnesium silicate hydrates. These include substances such as sugars, since in the presence of dissolved sugars, the formation of magnesium silicate hydrates can be reduced or avoided altogether. Certain organic additives are also suitable. All of these substances should be mixed or added in dissolved form before the solids are formed.
[0074] The reaction with CO2 is carried out by diffusion of the gas into the solid and the formation of magnesium carbonate and / or magnesium carbonate hydrate. The diffusion of the gas into the solid is promoted by a high CO2 partial pressure. Therefore, the reaction is preferably carried out in a closed vessel, since otherwise the CO2 partial pressure would drop again.
[0075] Sealed steel vessels, also known as autoclaves, are particularly suitable, as they can withstand high pressures and can also be operated at high temperatures. The CO2 can be fed to the autoclave filled with the solid in a pure or diluted state. For this purpose, it is beneficial if the CO2 originates from exhaust gases or exhaust air from manufacturing plants, which results in an elevated CO2 partial pressure compared to normal air.
[0076] Such flue gases are produced, for example, in steel mills, glass factories, cement kilns, fossil fuel-fired power plants and other industrial processes. The CO2 content of flue gases is often between 5% and 30% by volume. The use of these gases is advantageous, since increasing the CO2 concentration and compressing the gas is sufficient to allow the CO2 to bind to the solids in the autoclave.
[0077] This makes it possible to achieve CO2 partial pressures in the autoclave of between 0.1 bar and 15 bar. To accelerate the CO2 absorption process in the autoclave, the CO2 can be separated from the air or from the aforementioned exhaust gases and introduced in an almost pure state into the autoclave. The separation can be carried out using conventional methods such as amine washing or calcium looping. This means that higher CO2 partial pressures of between 1 bar and 50 bar can be achieved in the autoclave. To facilitate technical application, the pressure should be below 10 bar.
[0078] The formation of magnesium carbonate can be accelerated by increasing the temperature. This also increases the CO2 partial pressure in the autoclave. Another advantage of increasing the temperature is that it favors the formation of anhydrous magnesium carbonate (magnesite, MgCO3) instead of hydrated magnesium carbonate (nesquehonite, MgCO3·3H2O).
[0079] The temperature should be at least 25°C, preferably 50°C, but less than 70°C.
[0080] The production of magnesite is also promoted if magnesite nuclei are added by mixing into the dehydrated starting product before the solids are pressed. The solids should be treated in an autoclave for at least 4 hours, preferably 12 hours, and better still 24 hours, the atmosphere should be saturated with water, and / or the CO2 partial pressure should be kept permanently at a high level, and the bound CO2 is replaced by supplying fresh CO2.
[0081] If it is desired to contact the dehydrated starting product with CO2 prior to pressing and compressing, this can be done by bubbling a gas containing CO2 through the aqueous suspension.
[0082] The contact with CO2 can be carried out in a closed vessel such as a scrubber or autoclave, in which a suspension of water (possibly containing additives) and the dehydrated starting product in powder form, for example reinforced serpentine, is placed. Here too, the atmosphere can be saturated with respect to water vapor. Substances can also be added to promote the CO2 binding reaction.
[0083] These substances, such as citric acid, acetic acid or KH2PO4, can promote the binding of CO2, for example by buffering the pH value to less than 8.0, preferably less than 7.0, and even better less than 6.0. Magnesium silicate hydrate is present in low amounts. In addition, substances can be added that inhibit the formation of magnesium silicate hydrate and thus promote the formation of magnesium carbonate or magnesium carbonate hydrate. These include, for example, sugars and certain organic additives. NaCl should not be added to the solution, as it slows down or prevents the reaction. The addition of magnesite nuclei is recommended.
[0084] The suspension is preferably continuously moved. This can be done by using an agitator. In addition, a gas containing CO2 can be blown into the suspension. This can be air, flue gas, other waste gases from industrial processes, or pure CO2. A CO2 partial pressure of 0.0003 bar, advantageously 0.0010 bar, more advantageously 0.0100 bar, and particularly advantageously 0.3000 bar is sufficient for the reaction. In order to be able to reduce the requirements for the mechanical stability of the vessel, the total pressure should be less than 10 bar, preferably less than 2 bar. The CO2 partial pressure should be less than 0.5 bar in order to reduce the effort required to enrich CO2 in the gas introduced.
[0085] In suspension, the dehydrated starting product reacts with the introduced CO2 and magnesium carbonate or magnesium carbonate hydrate to form amorphous SiO2 (equation 5). In some cases, the formation of magnesium silicate hydrate can occur as a competing reaction.
[0086] It is advantageous if the operating temperature of the treatment units, especially the scrubber, is higher than room temperature, since this accelerates the chemical reactions. This heating can be achieved, for example, by introducing hot flue gases. The temperature in the scrubber should be at least 30°C, preferably 50°C. However, the solubility of CO2 decreases with increasing temperature, so the temperature increase should be limited to 70°C. The process can be carried out at very low CO2 partial pressures, preferably below 0.5 bar.
[0087] Preferably, the contact with CO2, the formation of the suspension and the precipitation of the resulting magnesium carbonate or magnesium carbonate hydrate can be carried out ideally simultaneously in one vessel, also called a reactor. Thus, a single-stage process can be provided in which the reaction is preferably carried out in only one vessel, for example an autoclave. This simplifies the whole process, especially in industrial applications, because, on the one hand, multiple reactors, possibly different reactors, are not used in the downstream process, and, on the other hand, time-consuming separation of the individual intermediate products is not required. Also, there is no need to pump the suspension.
[0088] It is advantageous if the dehydrated starting product that has been contacted with CO2 is subsequently separated from the aqueous suspension and, optionally, subjected to a heat treatment (preferably in an autoclave), especially when more than 20% by weight of magnesium carbonate hydrate, e.g. nesquehonite, is present.
[0089] The remaining solution can be reused to continue the sequestration process with new dehydrated starting product. The solid material in the form of the dehydrated starting product that has been contacted with CO2 can be further processed in dried or undried form.
[0090] It is advantageous that the dehydrated starting product contacted with CO2, also called sequestration product, contains anhydrous magnesium carbonate (magnesite) and that the proportion of magnesium carbonate hydrate, for example nesquehonite, should not exceed 20% by weight of the total substance, or even better less than 10% by weight. If the proportion of magnesium carbonate hydrate after sequestration is too high, a heat treatment can be carried out after the reaction with CO2 in order to convert the magnesium carbonate hydrate to anhydrous magnesium carbonate. This can be done, for example, by treatment in an autoclave at 100°C to 200°C or by drying at 150°C to 300°C.
[0091] As already mentioned, before pressing and compacting and after separation from the aqueous suspension, Al2O3, alkali or substances which introduce CaO in reactive form, dehydrated magnesium silicate hydrate and / or organic binders can be added and homogenization can be carried out.
[0092] 0.1m 2 It is preferred to subject the starting product to grinding, especially wet grinding, in order to provide a starting product with a fineness corresponding to or finer than the BET surface area of 1000 / g.The starting product is obtained at least partially without a higher fineness, even if it is already partially very fine due to natural weathering.This fineness can be easily increased by grinding.Wet grinding is also preferred here, since it is often more energy-efficient than dry grinding.
[0093] Furthermore, the present invention relates to an aggregate comprising magnesium carbonate hydrate and / or magnesium carbonate produced by the method according to the invention.
[0094] The aggregates are inert and can be further processed into concrete together with hydraulic binders such as cement clinker. For this purpose, further crushing may be necessary. In principle, the sequence of the method according to the invention is advantageous, at least if the starting product does not contain cement clinker. In particular, this can mean that it has no or almost no (less than 0.1% by mass) alite and / or belite phases. Experience has shown that materials present in cement clinker partially retard the reactions described herein, so their presence is undesirable. However, in small amounts, cement clinker is harmless.
[0095] Optionally, other substances can be added to the mix to improve the reactivity or modify the properties of the hardened material. These substances include organic additives, especially superplasticizers, rock powders, especially limestone, dolomite and olivine, pozzolanic additives, such as trass, glass powder, hard coal fly ash and / or thermally activated clays.
[0096] The starting product provided by the present invention is usually not a pure substance, so there are a large amount of impurities.However, it is advantageous that at least the molar ratio of Mg to Ca is 10:1 or more, and / or the molar ratio of Si to Al is also 10:1 or more.It has been shown that when calcium and aluminum are present with respect to magnesium and silicon, respectively, the reaction slows down or even stops completely.Therefore, it is not important to shift the corresponding molar ratios significantly toward magnesium or silicon.Preferably, the molar ratio of Mg to Ca is at least 20:1, and / or the molar ratio of Si to Al is at least 20:1.
Claims
1. a) providing a starting product comprising at least 20% by weight of magnesium silicate hydrate and 2 - crushing, in particular grinding, to a fineness corresponding to a BET surface area of 1.0 g / g or finer than this; b) homogenizing the starting product; c) at least partially dehydrating said starting product from bound water by means of a thermal treatment in a thermal treatment unit, during which the transformed starting product is treated at a temperature between 180° C. and 1000° C., After step c), the magnesium silicate hydrate present in the dehydrated starting product is at least partially dehydrated, thereby being converted into the dehydrated magnesium silicate hydrate, d) Reacting the dehydrated starting product with CO 2 and contacting said CO 2 is reacted with the dehydrated magnesium silicate hydrate to form magnesium carbonate hydrate and / or magnesium carbonate; e) before or after step d) pressing and compressing the dewatered starting product into a solid mass to produce aggregate.
2. The heat treatment of the starting product is carried out at a temperature of at least 550° C. and / or at most 750° C., 2. A method for producing aggregates according to claim 1, wherein the starting product is heat treated for at least 15 minutes, preferably for 30 minutes, more preferably for at least 60 minutes.
3. The method of claim 1 , wherein the heat treatment unit has an essentially homogenous temperature distribution.
4. The method for producing aggregate according to claim 1 , wherein a rotary kiln, in particular an indirectly heated rotary kiln without a direct flame in a reaction chamber, is used as the heat treatment unit.
5. 1mm 3 ~30,000mm 3 2. The method of claim 1, wherein the pressing and compressing are performed to form the solid body having a volume of
6. 2. The method of claim 1, wherein the pressing and compacting are carried out to form a solid body having a porosity of less than 20% by volume, preferably less than 10% by volume.
7. 2. A method for producing aggregates according to claim 1, wherein the solid material is heat treated at a temperature of at least 40°C, preferably at least 60°C, for at least 2 hours, in particular at least 24 hours.
8. The dehydrated starting product and the CO 2 2. The method of claim 1, wherein the contacting with is carried out in a closed vessel, in particular an autoclave, a scrubber or an overpressure vessel.
9. The dehydrated starting product and the CO 2 The contacting with at least 0.1 bar of CO 2 carried out at partial pressure, or The dehydrated starting product and the CO 2 The contact with is at least 0.0003 bar, preferably at least 0.0010 bar of CO 2 The method of claim 1 , carried out at partial pressure.
10. The dehydrated starting product and the CO 2 2. The method of claim 1, wherein said contacting with is carried out at a temperature of at least 30°C, preferably above 50°C.
11. The dehydrated starting product and the CO 2 2. The method of claim 1, wherein a substance such as sugar or other organic additive is added to the dehydrated starting product prior to or during said contact with, thereby reducing the formation of magnesium silicate hydrate.
12. The dehydrated starting product and the CO 2 The contacting with the CO 2 The method for producing aggregate according to claim 1, wherein the method is carried out by blowing a gas containing
13. The CO 2 is separated from the aqueous suspension and optionally subjected to a heat treatment, preferably in an autoclave, especially when more than 20% by weight of magnesium carbonate hydrate is present.
14. Prior to the pressing and compacting in step e) and after the separation from the aqueous suspension, reactive forms of Al 2 O 3 14. The method for producing aggregate according to claim 13, further comprising the steps of adding an alkali or CaO-introducing agent, the dehydrated magnesium silicate hydrate, and / or an organic binder, and homogenizing the mixture.
15. 15. An aggregate prepared by the manufacturing method according to any one of claims 1 to 14, comprising said magnesium carbonate hydrate and / or said magnesium carbonate.